Socialization Regarding the Implementation of Electronic Medical Records Based on the Republic of Indonesia Minister of Health Regulation - Dewi Oktavia; Annisa Wahyuni (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Electronic Medical Records are Medical Records created using an electronic system intended for the maintenance of Medical Records. Every Health Service Facility is required to maintain Electronic Medical Records. The aim of regulating medical records is to improve the quality of health services, provide legal certainty in the administration and management of medical records, guarantee the security, confidentiality, integrity, and availability of medical record data; and organize and manage digital-based and integrated medical records. Based on the initial survey at the Nanggalo Community Health Center, information was obtained that the medical records at the community health center did not yet use electronic medical records. Therefore, it is necessary to provide socialization regarding the regulations of the Minister of Health of the Republic of Indonesia Number 24 of 2022 concerning medical records to increase the knowledge of medical record officers and all health service providers at health centers. This service aims to provide socialization regarding the application of medical records based on Minister of Health Regulation Number 24 of 2022. The expected benefits are to increase the level of knowledge of medical record officers, nurses, doctors, and other electronic health officers regarding the mandatory implementation of Electronic Medical Records in health centers. Nanggalo. This community service will be carried out in June 2023 at the Nanggalo Community Health Center. This Community Service activity is carried out by providing outreach regarding the rules for Electronic Medical Records at the Nanggalo Community Health Center. From the socialization, there was an increase in participants' knowledge and understanding regarding the material with the average pre-test assessment result being 46 points while the post-test score increased to 86 points. It is recommended that this socialization activity has a positive impact on the progress of the Nanggalo Community Health Center and can implement electronic medical records at the Community Health Center by the regulations that all health facilities including community health centers can implement the use of electronic medical records.